The effect of sunk cost, framing effect, and educational background on the escalation of commitment - Permatasari, Astria Wulan; Budiarti, Laeli; Srirejeki, Kiky (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2020)
The purpose of this study is to examine whether negative framing and sunk costs affecting the escalation of commitments with an educational background as moderating variable. The study uses an experimental study approach with 2 x 2 x 2 within-subjects design. There were 39 managers from a state-owned enterprise who participated in this experiment. The result indicates that sunk costs and negative framing effect the escalation of commitment. In contrast, the educational background did not moderate the relationship between sunk cost and negative framing to the escalation of commitment.